1994
DOI: 10.1071/rd9940669
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes to uterine collagen types I, III and V in relation to early pregnancy in the rat

Abstract: Uterine tissues of pregnant rats were extracted to define any changes to the proportions of collagens types I, III and V. The total concentration of extracted collagen was determined in tissue samples from implant and adjacent non-implant (NI) sites. Extracts were also subjected to polyacrylamide gel electrophoresis (PAGE), immunoblotting and gel densitometry to define the collagen types and to determine their relative proportions. By relating the proportions to the collagen concentrations in the extracts, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…This is in contrast to recent findings in the goat, where collagen type I is diffusely arranged throughout the uterine stroma and does not exhibit any differences in intensity or distri- bution of immunostaining [Guillomot, 1999]. The abovementioned subepithelial meshwork of this fibre type seems to be a species-specific feature, since it has not been reported from other species such as humans [Aplin et al, 1988;Stovall et al, 1992], rats [Hurst et al, 1994] and goat [Guillomot, 1999]. During pregnancy this thin web of collagen type I fibres increases to a thick subepithelial membrane which should increase the tensile strength of the uterine wall carrying the growing fetus [Stelljes et al, 1998].…”
Section: Discussioncontrasting
confidence: 54%
“…This is in contrast to recent findings in the goat, where collagen type I is diffusely arranged throughout the uterine stroma and does not exhibit any differences in intensity or distri- bution of immunostaining [Guillomot, 1999]. The abovementioned subepithelial meshwork of this fibre type seems to be a species-specific feature, since it has not been reported from other species such as humans [Aplin et al, 1988;Stovall et al, 1992], rats [Hurst et al, 1994] and goat [Guillomot, 1999]. During pregnancy this thin web of collagen type I fibres increases to a thick subepithelial membrane which should increase the tensile strength of the uterine wall carrying the growing fetus [Stelljes et al, 1998].…”
Section: Discussioncontrasting
confidence: 54%
“…Type I collagen is the most common structural protein found in the body and is the most abundant collagen in the uterus. Type III collagen, which often colocalizes with type I collagen at a 1:5 ratio, is also widely distributed throughout the uterine muscle and is reported to be coregulated with collagen I [19,20]. It has also been reported that myometrial remodeling during pregnancy involves a controlled collagenolysis, evidenced by the disruption and partial degradation of collagen fibrils in late pregnancy [21,22].…”
Section: Discussionmentioning
confidence: 94%
“…Collagen a2 (VI) chain Expression levels of family members decreased in implantation sites (68). Collagen a1 (VI) chain Expression levels of family members decreased in implantation sites (68).…”
Section: Murinoglobulinmentioning
confidence: 95%